Apurinic/Apyrimidinic Endonuclease 1 Restricts the Internalization of Bacteria Into Human Intestinal Epithelial Cells Through the Inhibition of Rac1 - den Hartog, Gerco; Butcher, Lindsay D.; Ablack, Amber L.; Pace, Laura A.; Ablack, Jailal N. G.; Xiong, Richard; Das, Soumita; Stappenbeck, Thaddeus S.; Eckmann, Lars; Ernst, Peter B.; Crowe, Sheila E. (Frontiers in Immunology, 2021)
Pathogenic intestinal bacteria lead to significant disease in humans. Here we investigated the role of the multifunctional protein, apurinic/apyrimidinic endonuclease 1 (APE1), in regulating the internalization of bacteria into the intestinal epithelium. Intestinal cancer-derived epithelial cells and primary human epithelial cells were infected with Salmonella enterica serovar Typhimurium or adherent-invasive Escherichia coli. The effects of APE1 inhibition on bacterial internalization, the regulation of Rho GTPase Rac1 as well as the epithelial cell barrier function were assessed. Increased numbers of bacteria were present in APE1-deficient colonic tumor and primary epithelial cell lines. Activation of Rac1 was augmented following infection but negatively regulated by APE1. Pharmacological inhibition of Rac1 reversed the increase in intracellular bacteria in APE1-deficient cells whereas overexpression of constitutively active Rac1 augmented the numbers in APE1-competent cells. Enhanced numbers of intracellular bacteria resulted in the loss of barrier function and a delay in its recovery. Our data demonstrate that APE1 inhibits the internalization of invasive bacteria into human intestinal epithelial cells through its ability to negatively regulate Rac1. This activity also protects epithelial cell barrier function.